New system for predicting the outcome of secondary peritonitis - Nikolay V. Lebedev; Sariya B. Agrba; Vasily S. Popov; Alexey E. Klimov; Giorgy T. Svanadze (Russian Open Medical Journal)
Despite improvements in the methods of diagnostics, surgical interventions and intensive care, the problem of treating patients with diffuse peritonitis remains relevant. Diffuse peritonitis is a major contributor to mortality in all urgent care settings and the second leading cause of sepsis in critically ill patients. At the same time, even in developed countries, the number of patients with peritonitis does not tend to decrease, and mortality rates remain high, reaching 90-93% with the development of abdominal sepsis and toxic shock syndrome. One of the ways to reduce mortality in peritonitis is the use of objective systems for prognosis of the peritonitis outcome, allowing to compare the results of patient treatment and to choose the optimal treatment tactics for each particular patient. The objective — To develop a new system for predicting the outcome of secondary peritonitis (survival or death) focused on the criteria of abdominal sepsis and multiple organ dysfunction syndrome (associated or not associated with peritonitis), and to analyze its accuracy versus the most common comparable systems. Material and Methods — Our study was based on analyzing the treatment outcomes in 352 patients with secondary diffuse peritonitis. On admission, sepsis was diagnosed in 15 (4.3%), and toxic shock in 4 (1.1%) patients. The main causes of death were purulent intoxication and/or sepsis (51 cases or 87.9%), cancer intoxication (4 cases or 6.9%), and acute cardiac failure (3 cases or 5.2%). We analyzed the effectiveness of several systems of predicting the peritonitis outcomes: the Mannheim’s Peritoneal Index (MPI), World Society for Emergency Surgery Sepsis Severity Score (WSES SSS), Acute Physiology and Chronic Health Evaluation II (APACHE II) system, general Sequential Organ Failure Assessment Score (gSOFA), as well as the Peritonitis Prognosis System (PPS) developed by the authors. The probability of the effect of 40 clinical and laboratory parameters on the outcome of patients with secondary peritonitis was analyzed via using parametric and nonparametric methods of statistical analysis (Fisher’s test, Mann-Whitney U test, Chi-squared test with Yates’s continuity correction). The criteria were selected that had a predictive power for the lethal outcome (p <0.05), and they were included in the PPS system. To compare the predictive value of the PPS, ROC analysis was conducted with construction of receiver operating characteristic curves for each analyzed system of predicting the peritonitis outcome. The STATISTICA 8 software was used for performing the statistical analysis. Results — The following criteria were of greatest importance in predicting the lethal outcome: a patient’s age, a presence of a malignant neoplasm, a nature of the exudate, the development of sepsis (toxic shock), as well as multiple organ dysfunction not associated with the developed peritonitis. PPS exhibited the greatest accuracy in terms of predicting mortality in patients with secondary diffuse peritonitis (AUC=0.942) versus minimal in APACHE II (AUC=0.840). Conclusion — APACHE II, MPI, WSES SSS and PPS can be considered reliable in terms of mortality prognosis in peritonitis patients. PPS has the greatest accuracy of predicting the mortality in patients with secondary diffuse peritonitis (94%).